OPEN DATA MANAGEMENT ISSUES FOR GEOGRAPHIC INFORMATION SYSTEMS - Aydınoğlu, Arif Çağdaş (Stef92 Technology Ltd, 2016)
In Geographic Information Systems (GIS) applications, the interoperability of data sets is required to share geo-data sets coming from various sources and to make systems work together. Thus International Standardization Organization/Technical Committee 211 (ISO/TC211) standards support Model-driven Architecture for geographic data interoperability. By using Unified Modeling Language (UML), interoperable application schemas are designed for geographic data themes. Geographic Markup Language (GML) based data interchange model is produced from implementation-neutral UML models supporting multiple uses of geographic data. In this study, to test the applicability of interoperable data models, data transformation tools were developed and applied for some applications including disaster risk management. Additional data transformation tools were developed. It was examined that developing these tools is laborious and effective data management has difficulty, while open geographic data model is essential for the interoperability.
16th International Multidisciplinary Scientific Geoconference (SGEM 2016) -- JUN 30-JUL 06, 2016 -- Albena, BULGARIA
Keywords: Data and systems interoperability; ISO/TC211; OGC; UML; GML; open data